Evaluation of Qur'an Memorization Learning with The Tasmi’ Juziyyah Method to PPTQ Al Rasyid Kartasura Students - Dzulqornain Dzulqornain; Ahmad Nurrohim (Universitas Muhammadiyah Surakarta, 2025)
The learning process is always related to evaluation, this process is carried out to assess the extent to which learning has taken place. If the process goes well, the results that will be obtained will also be good. There are many methods or ways that can be used to evaluate learning, one of which in this discussion is the tasmi' juziyyah method. . This study aims to assess how effective the tasmi' juziyyah method is in learning to memorise the Qur'an for students at the Al Rasyid Qur'an Tahfidzul Islamic Boarding School. This research involves analysing the learning of memorising the Qur'an, and the impact of using the tasmi' juziyyah method. The method used by the author in collecting data is by conducting observations and direct interviews with the ketahfidzan section of PPTQ Al Rasyid. The results showed that the evaluation of students‘ memorisation through the tasmi’ juziyyah method was carried out in the form of a one juz memorisation deposit directly after the students completed their memorisation. If the students successfully pass this test, they can continue to the next juz. This research is expected to provide a deeper understanding of how effective the tasmi‘ juziyyah method is in evaluating the students’ memorisation process at PPTQ Al Rasyid.